Violence, identity, and self-determination - Vries, A. de (Stanford University Press, 1997., 1997)
"With the collapse of the bipolar system of global rivalry that dominated world politics after the Second World War, and in an age that is seeing the return of "ethnic cleansing" and "identity politics," the question of violence, in all of its multiple ramifications, imposes itself with renewed urgency. Rather than concentrating on the socioeconomic or political backgrounds of these historical changes